Comparing Traditional and Haptic Controllers for Fine-Movement Tasks in Virtual Reality - Boffi, Paolo; Clerici, Monica; Mauri, Giuseppe; Meneghin, Giulia; Gallace, Alberto; Lanzi, Pier Luca (SeGAH ... IEEE ... International Conference on Serious Games and Applications for Health (Online), 2024)
We investigate the usability of standard and haptic controllers for fine-movement tasks in virtual reality. We created an adaptation of the board-game Operation for head mounted displays in which players could interact either with the standard controllers (shipped with the visor) or a haptic controller-the tactically enhanced Geomagic Touch { }^{TM} X. Operation is a popular board game for children 6+ that tests the players hand-eye coordination and fine motor skills with simple yet challenging tasks. Following a between-subjects design, we evaluated the two types of controllers in terms of user experience and training effectiveness with 30 subjects. We performed a comprehensive evaluation using both quantitative scales and qualitative feedback. Our results show an overall satisfactory level of usability and few statistically significant differences in completion times and number of errors between the two controller models.